Evidence for Tunisian‐Like Pestiviruses Presence in Small Ruminants in Italy Since 2007. Issue 4 (3rd April 2016) - Ciulli, S.; Purpari, G.; Agnello, S.; Di Marco, P.; Di Bella, S.; Volpe, E.; Mira, F.; de Aguiar Saldanha Pinheiro, A. C.; Vullo, S.; Guercio, A.
Summary: The genus Pestivirus, which belongs to the Flaviviridae family, includes ssRNA+ viruses responsible for infectious diseases in pigs, cattle, sheep, goats and other domestic and wild ruminants. Like most of the RNA viruses, pestivirus has high genome variability with practical consequences on disease epidemiology, diagnosis and control. In addition to the officially recognized species in the genus Pestivirus, such as BVDV‐1, BVDV‐2, BDV and CSFV, other pestiviruses have been detected. Furthermore, most of the ruminant pestiviruses show low or absent species specificity observed in serological tests and are able to infect multiple species. Particularly, small ruminants are receptive hosts of the most heterogeneous group of pestiviruses. The aim of this study was to carry out the molecular characterization of pestiviruses isolated from sheep and goats in Sicily, Italy. Phylogenetic analysis of two viral genomic regions (a fragment of 5′‐UTR and the whole N pro regions) revealed the presence of different pestivirus genotypes in the analysed goat and sheep herds. Two of five viral isolates were clustered with BVDV‐1d viruses, a strain widespread in Italy, but never reported in Sicily. The other three isolates formed a distinct cluster with high similarity to Tunisian isolates, recently proposed as a new pestivirus species. This represents the first evidence for Tunisian‐like pestivirus presence in small ruminants in Italy. Furthermore, one of the isolates was collected from a goat, representing the first isolation of Tunisian‐like pestivirus from this species.